URGENSI IMPLEMENTASI ASAS ULTIMUM REMIDIUM TERHADAP TINDAK PIDANA PENYALAHGUNAAN IZIN TINGGAL KEIMIGRASIAN - Gilang Arizona, (2023)
This study aims to determine how the implementation of the ultimum remedium principle on crimes of Abuse of Permission to Stay Immigration. The immigration law is an administrative penal law, so administrative sanctions must be prioritized. In this study there are examples of cases of differences in the provision of sanctions. Then how the immigration crime can be applied to administrative sanctions or criminal sanctions. The factors that become benchmarks and cause differences in the imposition of sanctions on immigration crimes are the substance factors in the immigration law, because the formulation of the article is vague without clear boundaries in the preference for the use of sanctions for that reason, it is necessary to formulate the immigration law regarding the limitations of application. administrative sanctions and criminal sanctions.